Mountain wetland soil carbon stocks of Huascarán National Park, Peru - Chimner, Rodney A.; Resh, Sigrid C.; Hribljan, John A.; Battaglia, Michael; Bourgeau-Chavez, Laura; Bowser, Gillian; Lilleskov, Erik A. (Frontiers in Plant Science, 2023)
Although wetlands contain a disproportionately high amount of earth’s total soil carbon, many regions are still poorly mapped and with unquantified carbon stocks. The tropical Andes contain a high concentration of wetlands consisting mostly of wet meadows and peatlands, yet their total organic carbon stocks are poorly quantified, as well as the carbon fraction that wet meadows store compared to peatlands. Therefore, our goal was to quantify how soil carbon stocks vary between wet meadows and peatlands for a previously mapped Andean region, Huascarán National Park, Peru. Our secondary goal was to test a rapid peat sampling protocol to facilitate field sampling in remote areas. We sampled soil to calculate carbon stocks of four wetland types: cushion peat, graminoid peat, cushion wet meadow, and graminoid wet meadow. Soil sampling was conducted by using a stratified randomized sampling scheme. Wet meadows were sampled to the mineral boundary using a gouge auger, and we used a combination of full peat cores and a rapid peat sampling procedure to estimate peat carbon stocks. In the lab, soils were processed for bulk density and carbon content, and total carbon stock of each core was calculated. We sampled 63 wet meadows and 42 peatlands. On a per hectare basis, carbon stocks varied strongly between peatlands (avg. 1092 MgC ha-1) and wet meadows (avg. 30 MgC ha-1). Overall, wetlands in Huascarán National Park contain 24.4 Tg of carbon with peatlands storing 97% of the total wetland carbon and wet meadows accounting for 3% of the wetland carbon in the park. In addition, our results show that rapid peat sampling can be an effective method for sampling carbon stocks in peatlands. These data are important for countries developing land use and climate change policies as well as providing a rapid assessment method for wetland carbon stock monitoring programs.